CELL DYSTROPHY AND ITS TYPES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Dystrophy is a pathological process that leads to the loss or accumulation of substances in the tissues that do not normally belong to it (for example, the accumulation of coal in the lungs). With dystrophy, cells and intercellular substance are damaged, as a result of which the work of the diseased organ is disturbed. A complex of mechanisms - trophism - is responsible for maintaining metabolism and cell structure. It is he who suffers from dystrophy: the self-control of cells and the transport of metabolic products are disturbed.